Conservative Treatment of a Floating Mural Thrombus in the Descending Aorta - Goedemé, Johannes; Berzenji, Lawek; Nicolay, Simon; Hendriks, Jeroen M.H. (AORTA, 2021)
A 70-year-old woman was referred to the department of thoracic and vascular surgery after a floating mural thrombus was found in the distal aortic arch with extension into the proximal descending aorta. Imaging and clinical examination did not show signs of embolization and treatment with aspirin and low–molecular weight heparin was started. Follow-up after 2 weeks and 6 months showed a complete resolution of the aortic mural thrombus.
Keywords: floating thrombus; vascular surgery; aortic arch